An Analytical Study of the Administrative Development Efforts of the Education Sector in the Kingdom of Saudi Arabia in Light of the Requirements of the Fourth Industrial Revolution: Opportunities and Challenges (The International Journal for Scientific Research, 2024)
The study investigated into the efforts of administrative development in the education sector in the Kingdom of Saudi Arabia in light of the requirements of the Fourth Industrial Revolution, in search of opportunities to enhance it and the challenges facing the Kingdom in meeting the requirements of the Industrial Revolution in the fields of education and administrative development. This was accomplished through bringing the Fourth Industrial Revolution's concept, traits, elements, and difficulties as well as administrative development. Then, the study discussed the theoretical aspect compared to the practical reality of the education sector in the Kingdom of Saudi Arabia.Last but not least, the research determined and assessed the degree of compatibility and gap with the demands of the Fourth Industrial Revolution in relation to the state of the education sector in the Kingdom of Saudi Arabia at the time The research yielded several results, including: the practical applications in the Ministry of Education confirm the availability of the components of the Fourth Industrial Revolution, which enhance and develop the capabilities of the Kingdom in creating a physical environment and a generation capable of keeping up with the requirements of the Fourth Industrial Revolution. The Kingdom takes all measures and procedures to simplify processes, achieve equality, enhance transparency through artificial intelligence technologies, and reduce human intervention in the education sector.It also tends to create changes in qualitative skills by promoting and supporting areas of creativity and innovation in technical and artistic aspects, which supports the success of administrative development programs. Based on the previous results, the study recommends enhancing cloud computing services in the education sector through the development of community partnership programs with private sector institutions, increasing awareness programs and targeted messages to students and the community, and conducting workshops to raise awareness and national consciousness about the importance and mechanisms of data protection, while addressing the difficulties that hinder the effective implementation of artificial intelligence technologies, such as network weaknesses. Additionally, formulating a strategic vision to improve administrative work areas and develop human capabilities in the Kingdom of Saudi Arabia by developing smart learning methods that enhance capabilities and develop the required skills.
Keywords: Fourth Industrial Revolution; Kingdom of Saudi Arabia; Administrative development; Ministry of Education